(untitled) (Scientific journal of the Fergana State University, 2024)
The article provides theoretical pedagogical instructions of educators on such issues as family lifestyle customs, national values in the upbringing of children in the family in national mukhit, issues related to child education in the adaptation of children to social welfare, features of traditional folk education and related Customs and rituals, methods of National Education, features of the educational environment in the family, In a separate family, a new scientific direction and research is being carried out on the upbringing of the interaction of children on the basis of national values and traditions. At this point, it is important to scientifically study the system necessary for children in the family in the upbringing of their relationship based on national values and traditions. Obviously, in families, rich experience in preparing children for social life has been accumulated in our country, R & D has been well established and positive work has been paying off, in this regard, it is natural that the results of our research work also make a worthy contribution. Consequently, the essence of foreign experiences in the family on the issues of raising children’s relationships on the basis of national values and traditions encouraged us to explore this area.